Improving Public Infrastructure in the Philippines - Komatsuzaki, Takuji (IMF Working Papers; Working Paper ;, 2016)
This paper explores the macroeconomic effects of improving public infrastructure in the Philippines. After benchmarking the Philippines relative to its neighbors in terms of level of public capital and quality of public infrastructure, and public investment efficiency, it uses model simulations to assess the macroeconomic implications of raising public investment and improving public investment efficiency. The main results are as follows: (i) increasing public infrastructure investment results in sustained gains in output; (ii) the effects of improving public investment efficiency are substantial; and (iii) deficit-financed increases in public investment lead to higher borrowing costs that constrain output increases over time, underscoring the importance of revenue mobilization.